Pengaruh Kompetensi Dan Komitmen Terhadap Kepuasan Kerja Pegawai: Studi Pada Salah Satu Instansi Di Kabupaten Bandung Barat - Adhie Fasha Nurhadian (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2019)
This research made to determine the effect of competence and commitment to employee job satisfaction in this study using a questionnaire with 71 respondents. The data analysis method uses path analysis. The results showed that there was an influence of competence and commitment to employee job satisfaction. The competency variable has a direct impact of 14.4%, an indirect effect through a commitment relationship of 10.4%, so the total result is 24.7%. Commitment has a direct effect of 29.7%, an indirect impact through its relationship with competency of 10.4%, so the overall effect is 40.1%. And the total result of Competence and Commitment to job satisfaction is 64.8%, and the overall impact of job satisfaction on employee performance is 72.3%.